Stretch yourself : a personalized journey to deepen your teaching practice - McLemore, Caitlin; Passeport, Fanny (International Society for Technology in Education, 2018)
"In this book, two award-winning young educators from opposite sides of the globe will guide teachers entering the profession on how to think about their ambitions; dare to take risks; and innovate in their daily practice of 21st century teaching. The authors will use the metaphor of yoga, which is all about process and practice, to illustrate their points. With this motif in mind, the book will be organized into three sections, each tied to an aspect of yoga: 1) Breathe, 2) Stretch, and 3) Meditate; and each section will be broken down into chapters exploring issues that all new teachers face, including: understanding and designing your emerging "you" through self-awareness and self-modification to achieve excellence; finding the courage to be your emerging "you" through self-assessment and planning strategies; the importance of taking risks and persevering in your practice; using tools available in the "edtech toolbox" to improve your teaching practice; tinkering, the importance of failure, and overcoming fear; the need for balance--and not overstretching; self-reflection and delivering feedback to students; and sharing your journey with others"--